2011
DOI: 10.1159/000328337
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Renal Abnormalities in Rats Exposed to Losartan during Lactation

Abstract: Background/Aims: Rats exposed to losartan during lactation exhibit progressive changes in renal function and structure. This study analyzed the early events in pups from dams that received losartan during lactation. Methods: Male Wistar rats from dams that received 2% sucrose (control, n = 25) or losartan (100 mg/kg/day) diluted in 2% sucrose (n = 33) during lactation were anesthetized 21 days after birth. Blood and urine samples were collected to assess renal function, and kidneys were removed for histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 71 publications
1
9
0
1
Order By: Relevance
“…We also observed an increase in FE + Na in rats that received losartan during renal development, which indicated that renal sodium transport was altered. The changes in glomerular filtration rate observed in the present study were similar to those observed in other studies that used this model (5,7,20,21).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We also observed an increase in FE + Na in rats that received losartan during renal development, which indicated that renal sodium transport was altered. The changes in glomerular filtration rate observed in the present study were similar to those observed in other studies that used this model (5,7,20,21).…”
Section: Discussionsupporting
confidence: 91%
“…The renin-angiotensin system (RAS) plays an important role in expansion, migration, and formation of renal structure during nephrogenesis (4). Results from our studies and others have shown that pharmacological RAS inhibition or genetic deletion of downstream signaling components of RAS (1,3,(5)(6)(7)(8) result in impaired development of glomeruli and preglomerular vasculature. Angiotensin II (ANGII) also affects the post-glomerular circulation.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations